An appraisal of the epidemiology of Trypanosoma cruzi serology in Brazil - M. F. Feitosa (Memórias do Instituto Oswaldo Cruz., 1991)
A large bibliographic survey provided data on Trypanosoma cruzi serology covering the period l948-l984. Epidemiological-demographic methods provided an estimate of 11% for the prevalenceof positive serology in Brazil, by 1984. Significant temporal trends were observed for most of the Brazilian geographical regions as well as for Brazil, as a whole. The parabolic curve that fit best for the entire country, indicates that by 1991, the incidence of new positive serology would be close to zero. This conclusion needs further fine-adjustment, since the forecast point is somewhat distant from the measured period.